Performance of wall-slab connection enhanced with steel fibres under reversible cyclic load / Nurharniza Abdul Rahman - Abdul Rahman, Nurharniza (Institute of Graduate Studies, UiTM, 2012)
The most critical stress concentration build-up in a tunnel-form construction is in the wall-slab connection at the first floor level. A total of twelve (12) wall-slab samples were cast, six (6) as anchorage connection and another six (6) as cross-bracing. All samples were tested under cyclic load using displacement control; six (6) samples under lateral and the remaining six (6) under vertical. Hooked end steel fibres (SteFib) were added in the concrete mix and placed at various locations in the wallslab samples.